The Chinese in America - Sung, Betty Lee (New York : MacMillan, 1972)
Examines the causes of Chinese immigration to the United States and describes the contributions of this ethnic group to the social, cultural, and economic life of their new country.
Bibliography: p. 115
Keywords: Chinese Americans -- Juvenile literature